2021
DOI: 10.1111/jzs.12575
|View full text |Cite
|
Sign up to set email alerts
|

Weak population‐genetic structure of a widely distributed nematode parasite of frogs in the western Palearctic

Abstract: The genetic structure of parasite populations is affected by various factors such as host–parasite interactions, life‐history strategies, and the evolutionary histories of both interacting organisms. In this study, we investigated the distribution, prevalence, and population‐genetic structure of Icosiella neglecta (Spirurida, Onchocercidae), a nematode parasite found in Ranidae frogs. We reported this parasite from eight species of water frogs (genus Pelophylax) in Europe, the Middle East, and Central Asia. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…The new sequence appeared to be identical to three of four other sequences from the country and 42 sequences from other parts of the western Palaearctic, particularly, from Eastern Europe, Transcaucasia, and several Balkan countries. We assume that the population-genetic structure of I. neglecta in Ukraine is weak and not associated with the geography of the species populations within the country, similar to that discovered by Mikulíček et al (2021) in the I. neglecta distribution area.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The new sequence appeared to be identical to three of four other sequences from the country and 42 sequences from other parts of the western Palaearctic, particularly, from Eastern Europe, Transcaucasia, and several Balkan countries. We assume that the population-genetic structure of I. neglecta in Ukraine is weak and not associated with the geography of the species populations within the country, similar to that discovered by Mikulíček et al (2021) in the I. neglecta distribution area.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, the nematode may be absent in some regions and frog populations due to the absence of its intermediate hosts and vectors, mainly Forcipomyia velox (Winnertz) (Ceratopogonidae) (Desportes, 1942). Mikulíček et al (2021) suggested that the vectors of I. neglecta might have contributed to the relatively recent spread of the parasite. The recent spread of I. neglecta in northern Ukraine is apparent from the comparison of the information from previous surveys in this region with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations